Cavitating Lesions around the Cochlea Can Affect Audiometric Threshold and Clinical Practice - Giulia Zambonini; Sara Ghiselli; Giuseppe Di Trapani; Daria Salsi; Domenico Cuda (Audiology Research, 2023)
There are several pathologies that can change the anatomy of the otic capsule and that can distort the bone density of the bony structures of the inner ear, but otosclerosis is one of the most frequent. Similar behavior has been shown in patients affected by osteogenesis imperfecta (OI), a genetic disorder due to a mutation in the genes coding for type I (pro) collagen. In particular, we note that otosclerosis and OI can lead to bone resorption creating pericochlear cavitations in contact with the internal auditory canal (IAC). In this regard, we have collected five cases presenting this characteristic; their audiological data and clinical history were analyzed. This feature can be defined as a potential cause of a third-window effect, because it causes an energy loss during the transmission of sound waves from the oval window (OW) away from the basilar membrane.